2018
DOI: 10.1055/s-0038-1673363
|View full text |Cite
|
Sign up to set email alerts
|

HIFU for Bone Metastases and other Musculoskeletal Applications

Abstract: High-intensity focused ultrasound (HIFU) is a totally noninvasive procedure that has shown promising results in the management of numerous malignant and nonmalignant conditions. Under magnetic resonance or ultrasound guidance, high-intensity ultrasound waves are focused on a small, well-defined target region, inducing biologic tissue heating and coagulative necrosis, thus resulting in a precise and localized ablation. This treatment has shown both great safety and efficacy profiles, and may offer a multimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…MR-HIFU delivers acoustic energy to heat tissue in a target area to ablative temperatures. The hypothetical mode of action of MR-HIFU for CIBP is ablation of periosteal nerves and tumor debulking [21] . MR-HIFU aims at palliative pain treatment and has been shown to be effective in inducing rapid and long-lasting pain relief with response rates ranging from 67% to 88% [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR-HIFU delivers acoustic energy to heat tissue in a target area to ablative temperatures. The hypothetical mode of action of MR-HIFU for CIBP is ablation of periosteal nerves and tumor debulking [21] . MR-HIFU aims at palliative pain treatment and has been shown to be effective in inducing rapid and long-lasting pain relief with response rates ranging from 67% to 88% [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…In this study response occurred within three days after MR-HIFU treatment [13] . Secondly, there may be a complimentary effect of MR-HIFU and EBRT, as both treatments have a slightly different mechanism of action [21] . Until now, there is no evidence available on the feasibility or safety of combined EBRT and MR-HIFU treatment.…”
Section: Introductionmentioning
confidence: 99%
“…MRI‐guided high intensity focused ultrasound (MR‐HIFU) allows non‐invasive treatments of various conditions 1 by thermal ablation, and its effectiveness for treatment of patients with painful bone metastases has been clinically demonstrated. 2 Pain reduction in these patients is achieved by ablation of the periosteum in the proximity of the metastases. MRI is a reliable guidance technique for HIFU, due to its excellent soft‐tissue contrast and its capacity to map tissue temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 MR-HIFU is a non-invasive image-guided treatment modality, which can deliver acoustic energy to heat target tissue to ablative temperatures. 11,13 One of many potential applications of MR-HIFU is in palliative pain treatment for CIBP, in which the pain palliation mechanism is hypothesized to be through ablation of periosteal nerves and tumor debulking. Previous studies have shown that pain response may occur within three days after MR-HIFU treatment, and response rates are promising with pain responses ranging from 67-88% of patients.…”
Section: Introductionmentioning
confidence: 99%